Introduction Theory and Practice Court Procedural Law Constitution - Saragih, Sepriandison; Gultom, Sarles; Moonti, Roy Marthen (Future Science / FSH-PH Publications, 2022)
Laws that develop in society sued the Court for follow development law these, including procedural law. Development procedural law of the Constitutional Court in practice need ijtihad from the Constitutional Court in skeleton find law new to use enforce supremacy constitution, democracy, justice and rights constitutional inhabitant country. Writing this use method approach juridical normative: that is the approach used for study or analyze secondary data in the form of materials primary law and materials law secondary Terms general procedural law arrange about provisions that are general, i.e provision about trial, conditions application, and regarding verdict. Provision in Thing trial in the Constitutional Court, for example, the Court examines, hears, and cut off in hearing plenary attended by all judges consisting of over 9 (nine) people, only in